HCV and HBV infection in Nigerian patients with liver cirrhosis and hepatocellular carinoma (2004)
Although efforts have made to determine the significance of Hepatitis B virus (HBV) infection in Nigerians with chronic liver diseases, the role Hepatitis C virus (HBV) infections in Nigerian patients with Liver Cirrhosis(LC) and Hepatocellular Carcinoma (HCC). The incidence of HBV and antibodies to HCV was determined by Enzyme Linked Immunosorbent Assay (ELISA) in 24 Nigerians Hepatocellular carcinoma (n=14), as well as healthy adult Nigerians who served as controls(n=14) at the University College Hospital, Ibadan. Incidence rates of 50%, 71% and 40% of HBsAg were obtained in patients with LC, HCC and Controls respectively while 20%, 14% and 20% were AntiHCV positive in the respective group (P<0.0005 for HCC). Co-infection by HBV and HCV was found in one patient with HCC. Infection by HCV occured in older age group (57.5_8 years) than HBV infection(47.8+4 years, P<).0.01) while both infections were commoner in male subjects. In summary, HBV infection is commoner than that of HCV in patients with HCC. However, both HBV and HCV might be contributory to the aetiology of LC and HCC. Efforts should be internsified at reducing the high prevalence of HBV infection as well as that of HCV in Nigerians by instituting active preventive measures.